Gladys Black letter to Nicholas S. Halmi regarding Snowy Owl sightings and Iowa Ornithologists' Union membership, January 24, 1977 - Black, Gladyset al (1977)
Snowy Owl sightings contributed by Gladys Black in a letter to Nicholas S. Halmi. Gladys is also commenting on a recent increase in Iowa Ornithologists' Union memberships. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of winter, 1976-1977. Epson - sheet feed/flatbed